Pengaruh Pengajaran Oleh Aṭṭhasīlanī Terhadap Minat Belajar Siswa Buddhis Di SD Taman Harapan - Pipit Ariyanti (Perspektif Ilmu Pendidikan, 2022)
Abstract: This research was conducted to determine the effect of Atthasilani's teaching on the learning interest of Buddhist students at Taman Harapan Elementary School. References to determine student learning interest can be measured through seven indicators according to Bahri (1-4) and according to Slameto (5-7), namely (1) feelings of pleasure, (2) student interaction, (3) interest, (4) student attention , (5) positive feelings while studying, (6) there is comfort while studying, and (7) the capacity to make decisions while studying. The design of this research is quantitative research which is supported by qualitative research. The instrument used is a written statement (questionnaire) with a Likert scale calculation and the t-test is supported by a list of interviews stated to 6 informants. The results of this study show that the interest in learning of Buddhist students in the teaching carried out by atthasilani mostly has an effective interest. However, based on the overall Likert scale calculation, teaching by subject teachers has the highest score of 40 and teaching by atthasilani has the lowest score of 25. Partially, there are several indicators that state high scores, some are moderate and some are even less. Thus, there are differences in teaching by atthasilani and teachers who state high gains on teachers so that there is no influence of teaching by atthasilani. Keywords: Teaching, Interest in learning